2011
DOI: 10.1038/nn.2736
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional omega-3 deficiency abolishes endocannabinoid-mediated neuronal functions

Abstract: The corollaries of the obesity epidemic that plagues developed societies are malnutrition and resulting biochemical imbalances. Low levels of essential n-3 polyunsaturated fatty acids (n-3 PUFAs) have been linked to neuropsychiatric diseases, but the underlying synaptic alterations are mostly unknown. We found that lifelong n-3 PUFAs dietary insufficiency specifically ablates long-term synaptic depression mediated by endocannabinoids in the prelimbic prefrontal cortex and accumbens. In n-3-deficient mice, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
258
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(280 citation statements)
references
References 50 publications
15
258
2
5
Order By: Relevance
“…The contribution of nutrients themselves and/or their metabolites in this process should be considered too. For instance, dietary fat-derived endocannabinoids are major components of the gut-brain axis and can engender synaptic alterations in the brain (Crosby et al, 2011;Lafourcade et al, 2011;Bermudez-Silva et al, 2012). On the other hand, it seems that stress-related signals are not involved in diet-induced hypothalamic plasticity because familiar conditions, like reexposure to HFD, still produced upregulation of the plasticity marker PSA, whereas food novelty was not sufficient to induce this response.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of nutrients themselves and/or their metabolites in this process should be considered too. For instance, dietary fat-derived endocannabinoids are major components of the gut-brain axis and can engender synaptic alterations in the brain (Crosby et al, 2011;Lafourcade et al, 2011;Bermudez-Silva et al, 2012). On the other hand, it seems that stress-related signals are not involved in diet-induced hypothalamic plasticity because familiar conditions, like reexposure to HFD, still produced upregulation of the plasticity marker PSA, whereas food novelty was not sufficient to induce this response.…”
Section: Discussionmentioning
confidence: 99%
“…Given the epidemiological and clinical data linking n −3 PUFAs deficiency with mood disorders (Parker et al, 2006), autoimmune diseases (Fernandes et al, 2008) and abnormal synaptic plasticity (Lafourcade et al, 2011), it is likely that n −3 PUFA may play a pivotal role in treating autoimmune disease and co-morbid mood disorders. Our data confirmed that 6 month old BAFF Tg mice display abnormal hippocampal progenitor cell proliferation (Crupi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, DHA is essential for normal development and function of the brain (30). Deficiency of DHA in the nervous system impairs synaptic transmission (31) and DHA supplementation may be protective against neurodegenerative diseases and psychiatric disorders (32,33).…”
mentioning
confidence: 99%